Autonomous Control of the Economic System - Kornai, Janos; Martos, Bela (Econometrica, 1973)
The possible impact of autonomous (vs. the price mechanism and directive control) on the functioning of an economic system is studied. It sheds some light on similarities among economic systems that are quite different in their higher functioning. The survival and stability conditions for a Leontief-type economy demonstrate the role stock signals can play in controlling the behavior of producers and consumers. COMPLICATED SYSTEMS FULFILLING a number of duties are controlled, generally, by multi-stage regulators consisting of both simple and complex mechanisms. For example, some of the functions of the spaceship are controlled by simple, built-in servomechanisms; others are guided half-automatically from the earth; and still others are guided directly by handpower of the astronauts. Or let us take a higher living organism, the human body, say. Some of its functions, respiration, digestion, blood circulation, functioning of the heart, lungs, stomach, intestines, and kidneys are controlled by the autonomous (vegetative) nervous system; other functions by the central nervous system. An economy is also a complicated system, fulfilling a great number of functions. Its processes are controlled by several kinds of mechanisms of low and high degree. The low degree following the physiological analogy, is called autonomous (vegetative) control.2 The first section of our study explains the idea of the control mechanism, draws comparisons between the different mechanisms, and presents some empirical findings. Sections 2 and 3 analyze the autonomous theoretically, with the aid of a general and a special model. In the fourth section we draw conclusions and comment on the previous theoretical analysis.